2017
DOI: 10.1556/2060.104.2017.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin regulates intracellular calcium release and inhibits oxidative stress parameters, VEGF, and caspase-3/-9 levels in human retinal pigment epithelium cells

Abstract: In this study, we aimed to observe whether curcumin (cur), a polyphenolic compound derived from the dietary spice turmeric, a yellow substance obtained from the root of the plant Curcuma longa Linn, has any protective effect against blue light irradiation in human retinal pigment epithelium (ARPE-19) cells. For this purpose, we evaluated the intracellular calcium release mechanism, poly ADP ribose polymerase (PARP), procaspase-3/-9 protein expression levels, caspase activation, and reactive oxygen species leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Ca 2+ overload in the mitochondria usually serves as intracellular signaling for PARP activation [35,36]. PARP activation leads to PARP-mediated mitochondrial dysfunction, as demonstrated by mitochondrial membrane depolarization, overproduction of superoxide, and loss of cardiolipin content [37].…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ overload in the mitochondria usually serves as intracellular signaling for PARP activation [35,36]. PARP activation leads to PARP-mediated mitochondrial dysfunction, as demonstrated by mitochondrial membrane depolarization, overproduction of superoxide, and loss of cardiolipin content [37].…”
Section: Discussionmentioning
confidence: 99%
“…Inactive forms of Casp -3 and Casp -9 locate in cytoplasm of cells, including ARPE19 [ 38 , 39 ]. In the pathways of apoptosis, Casp -3 and Casp -9 proteins have key roles.…”
Section: Resultsmentioning
confidence: 99%
“…TRPM2 and the absence of currents in the ARPE19-KO obviously evidenced the involvement of TPSO on TRPM2 activation in the ARPE19. Inactive forms of Casp -3 and Casp -9 locate in cytoplasm of cells, including ARPE19 [38,39]. In the pathways of apoptosis, Casp -3 and Casp -9 proteins have key roles.…”
Section: The Treatment Of Adpr Induced Trpm2 Activation In the Arpe19 But Not In The Arpe19-komentioning
confidence: 99%
“…In the patch-clamp experiments and laser confocal microscope analyses, we have observed increased levels of TRPM2 current density and Ca 2+ fluorescence intensity through oxidative stress (CPx) stimulation in Hep2 cells, but their density and intensity were decreased by TRPM2 channel blockers (ACA and 2-APB) in Hep2 cells. In recent studies, the protective role of CURC through the inhibition of TRPM2 channel were reported against excessive Ca 2+ entry into cytosol of different normal cells 29,30,3336 . However, accumulating evidence indicates that CURC has also pro-oxidant and calcium channel activating actions 20,21,37,38 .…”
Section: Discussionmentioning
confidence: 99%